2019
DOI: 10.1007/s12033-019-00155-9
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and Adaptation to Salt Stress of the REDOX-RESPONSIVE TRANSCRIPTION FACTOR 1 (RRTF1) Gene are Controlled by its Promoter

Abstract: The REDOX RESPONSIVE TRANSCRIPTION FACTOR 1 (RRTF1) gene encodes a member of the ERF/AP2 transcription factor family involved in redox homeostasis. The RRTF1 gene shows tissue-specific responsiveness to various abiotic stress treatments including a response to salt stress in roots. An interesting feature of this response is an adaptation phase that follows its activation, when promoter levels revert to a base line level, even if salt stress is maintained. It is unclear if adaption is controlled by a switch in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…The copyright holder for this this version posted December 20, 2020. ; https://doi.org/10.1101/2020.12.18.423458 doi: bioRxiv preprint fer-4 and herk1the1-4 might also be responsible for their amplified susceptibility to salt. Recently it was reported that ectopic over expression of RRTF1 is detrimental to plant salt tolerance [42]. This is consistent with our observations, where the higher RRTF1 expression pattern described in both salt-treated fer-4 or herk1the1-4 is linked to the higher plant salt susceptibility (Figure 1D/S1D).…”
Section: Herk1the1-4 and Fer-4 Mutants Are Affected In Early Responsesupporting
confidence: 93%
See 2 more Smart Citations
“…The copyright holder for this this version posted December 20, 2020. ; https://doi.org/10.1101/2020.12.18.423458 doi: bioRxiv preprint fer-4 and herk1the1-4 might also be responsible for their amplified susceptibility to salt. Recently it was reported that ectopic over expression of RRTF1 is detrimental to plant salt tolerance [42]. This is consistent with our observations, where the higher RRTF1 expression pattern described in both salt-treated fer-4 or herk1the1-4 is linked to the higher plant salt susceptibility (Figure 1D/S1D).…”
Section: Herk1the1-4 and Fer-4 Mutants Are Affected In Early Responsesupporting
confidence: 93%
“…To investigate whether the lack of FER or HERK1/THE1-4 had an effect on salt-induced gene expression levels, we selected three salt-induced marker genes [17], [40]- [42] and checked their expression in response to salt application.…”
Section: Herk1the1-4 and Fer-4 Mutants Are Affected In Early Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Promoters regulate gene expression mainly at the transcriptional level and are coordinated by a variety of cis -acting elements and trans-acting factors (Soliman & Meyer, 2019). We discovered a great deal of hormone responsive cis -acting components in the upper reaches regulatory sequences of PbPAL s family members (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that some families contain specific conservative motifs, which means that these specific conservative motifs may be necessary for the specific functions of the subgroup, such as motifs 20 to ClusterⅠfamily. Promoters regulate gene expression mainly at the transcriptional level and are coordinated by a variety of cis-acting elements and trans-acting factors (Soliman et al, 2019). We discovered a great deal of hormone responsive cis-acting components in the upper reaches regulatory sequences of PbPAL genes family members (Table S4).…”
Section: Discussionmentioning
confidence: 99%